2023
DOI: 10.3350/cmh.2022.0351
|View full text |Cite
|
Sign up to set email alerts
|

Causes and risk profiles of mortality among individuals with nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the United States and worldwide. Though nonalcoholic fatty liver per se may not be independently associated with an increased risk for all-cause mortality, it is associated with a number of harmful metabolic risk factors, such as type 2 diabetes mellitus, hyperlipidemia, obesity, a sedentary lifestyle, and an unhealthy diet. The fibrosis stage is a predictor of all-cause mortality in NAFLD. Mortality in individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…Furthermore, examining disease-specific mortality, each quintile increase resulted in HRs of 1.33 (1.31-1.35) for mortality due to cardiovascular disease, 1.23 (1.20-1.25) for mortality due to diabetes, and 1.22 (1.21-1.24) for mortality due to extrahepatic cancer ( Supplemental Table 22 ), all of which are known common causes of death in MASLD patients. 17 Significant associations for all-cause mortality also present in Bio Me , where each quintile increase in predicted score resulted in HRs of 1.13 (1.08-1.19) among all participants and 1.13 (1.07-1.19) among controls ( Figure 3c-d ; Supplemental Figure 1c-d ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, examining disease-specific mortality, each quintile increase resulted in HRs of 1.33 (1.31-1.35) for mortality due to cardiovascular disease, 1.23 (1.20-1.25) for mortality due to diabetes, and 1.22 (1.21-1.24) for mortality due to extrahepatic cancer ( Supplemental Table 22 ), all of which are known common causes of death in MASLD patients. 17 Significant associations for all-cause mortality also present in Bio Me , where each quintile increase in predicted score resulted in HRs of 1.13 (1.08-1.19) among all participants and 1.13 (1.07-1.19) among controls ( Figure 3c-d ; Supplemental Figure 1c-d ).…”
Section: Resultsmentioning
confidence: 85%
“…16 22), all of which are known common causes of death in MASLD patients. 17 Significant associations for all-cause mortality also present in BioMe, where each quintile increase in predicted score resulted in HRs of 1.13 (1.08-1. 19) among all participants and 1.13 (1.07-1.19) among controls (Figure 3c-d; Supplemental Figure 1c-d).…”
Section: Mortality Associationsmentioning
confidence: 92%
“…The leading cause of death in individuals with NAFLD is CVD ( 13 ). A recent meta-analysis reported that NAFLD was associated with a moderately increased risk of fatal or non-fatal CVD events (pooled HR: 1.45, 95% CI: 1.31–1.61).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Clinical and Molecular Hepatology, Konyn et al have presented the results of an extensive review of the current literature, focusing on the causes and risk profiles of mortality in patients with NAFLD. 5 Based on their findings, the authors have concluded that 1) NAFLD per se may not independently increase the risk of all-cause mortality; 2) the most common causes of death in patients with NAFLD include cardiovascular disease, extrahepatic cancer, liver disease, and diabetes; 3) risk factors for increased mortality in NAFLD are mutation in the patatin like phospholipase domain containing 3 (PNPLA3) gene, low thyroid function, and sarcopenia; and 4) dietary modification and physical activity leading to weight loss have a significant effect on decreasing the mortality.…”
mentioning
confidence: 99%
“…In the review by Konyn et al, an emphasis on the impact of diabetes on NAFLD is noteworthy, since mortality among patients with diabetes and chronic liver disease is increasing, while age-standardized mortality due to diabetes is declining. 5 According to the authors' recommendations, clinicians should be cognizant of the bidirectional impact of NAFLD and diabetes. (FibroScan-AST) for detecting significant fibrosis.)…”
mentioning
confidence: 99%